2020
DOI: 10.1111/poms.13146
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Buy‐Online‐and‐Pickup‐in‐Store in Omni‐Channel: Evidence from Customer Usage Data

Abstract: T he buy-online-and-pickup-in-store (BOPS) service has been widely treated by retailers as an important omni-channel initiative. However, few studies have attempted to quantify the impact of BOPS usage on subsequent purchase behaviors or examine the critical roles of offline stores in the value generation of BOPS. Thus, through 25,724 BOPS instances used by 16,202 unique customers via a hybrid retailer, this study investigated the impact of customers' BOPS usage on their online and offline purchase frequency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 44 publications
(95 reference statements)
0
58
0
Order By: Relevance
“…For each concept, we offer a series of research questions grounded in entrepreneurship research streams. The first concept is omni-channel , which refers to seeking to seamlessly integrate flows of the three main items that move through supply chains: products (e.g., finished goods, materials, operating supplies), information (e.g., product information, marketing material), and financial resources (e.g., purchases, refunds) (Song, Wang, Liu, & Li, 2020). This approach is usually associated with large corporations, but some small entrepreneurial firms use it, too.…”
Section: How Supply Chain Management Concepts Can Inform Entrepreneurmentioning
confidence: 99%
See 1 more Smart Citation
“…For each concept, we offer a series of research questions grounded in entrepreneurship research streams. The first concept is omni-channel , which refers to seeking to seamlessly integrate flows of the three main items that move through supply chains: products (e.g., finished goods, materials, operating supplies), information (e.g., product information, marketing material), and financial resources (e.g., purchases, refunds) (Song, Wang, Liu, & Li, 2020). This approach is usually associated with large corporations, but some small entrepreneurial firms use it, too.…”
Section: How Supply Chain Management Concepts Can Inform Entrepreneurmentioning
confidence: 99%
“…Strategic Management purchases, refunds) (Song, Wang, Liu, & Li, 2020). This approach is usually associated with large corporations, but some small entrepreneurial firms use it, too.…”
Section: Figure 1 Research Intersections Among Entrepreneurship Suppmentioning
confidence: 99%
“…BOPS usage, in turn, was shown to positively influence purchase size, repurchase intention, and purchase deferral (Chatterjee 2010 ). Specifically, Song et al ( 2020 ) found that BOPS usage increases both the purchase amount of online shopping and the purchase frequency of offline shopping. They also showed that offline store characteristics (i.e., store density, product variety, competition) moderate these benefits of BOPS on purchase behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers who utilize multiple channels are generally considered more valuable than single-channel customers to retailers because they are more loyal and spend more (Venkatesan et al 2007 ; Kushwaha and Shankar 2013 ; Sopadjieva et al 2017 ). Song et al ( 2020 ) found that BOPS usage generates significant additional economic value in both online and offline channels. Furthermore, the shopping experience during the physical encounter largely determines the customer-brand relationship due to its high level of intimacy (Bell et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in the number of management objects (management of information, knowledge, creative and innovative potential, customer relationships, etc.). [18] [20] This is especially true in connection with the development of the digitalization process and the formation of the economy 4.0. [13].…”
mentioning
confidence: 99%